If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy(xy + -1u) = 0 Reorder the terms: xy(-1u + xy) = 0 (-1u * xy + xy * xy) = 0 (-1uxy + x2y2) = 0 Solving -1uxy + x2y2 = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1x2y2' to each side of the equation. -1uxy + x2y2 + -1x2y2 = 0 + -1x2y2 Combine like terms: x2y2 + -1x2y2 = 0 -1uxy + 0 = 0 + -1x2y2 -1uxy = 0 + -1x2y2 Remove the zero: -1uxy = -1x2y2 Divide each side by '-1xy'. u = xy Simplifying u = xy
| .75x+4.50=1.25x+2.50 | | 4k=3.6 | | 1/25:3=x:12 | | sinx=0.927 | | 3k=8+4k | | 2w=3w+10 | | -6=x-14+7x | | .5(6x+10)=20 | | q+70=55 | | -35-x=31+5x | | 3t+3=6t+9 | | (5x^2+1)(6x^2+4)=1 | | G/3=3.9 | | 3(x-5)-4(2x-3)=7 | | (2y+3y)2= | | x-.85x=32.89 | | 6a-10+5a=6a+20 | | 5+1.5(2m-1)=0.5 | | 5n+35+50=160 | | 58=1/2-x | | Sqrt(-7-7x)+3=10 | | 2/5x+1/10=1/2(x+4) | | 6a-10a+5a=6a+20 | | 58=1/2x | | 11pq(5p-7q+4)= | | 8x/4=12 | | -20+-3x=-12x+7 | | 1/2(4-x)=2/5 | | 43-n+16=44 | | 22=9+6(h+8) | | x-4=156 | | 1-4+5=2 |